“My Family Was Also Happy”: Couples’ Qualitative Reports of a Combined Behavioral Economics and Cognitive Behavioral Therapy Intervention to Reduce Alcohol Use and Intimate Partner Violence - Mette, Miriam (Violence against women, 2024)
Improving intimate partner violence interventions requires understanding pathways to change among couples participating in these interventions. This article presents qualitative data from 18 males and 16 females who participated in a combined behavioral economics (contingency management) and cognitive behavioral therapy alcohol and violence reduction intervention trial in Bengaluru, India. Results confirmed several theorized pathways of change, as well as identified further mechanisms through which the intervention supported the change. These included the emotional impacts of incentives, perceived and actual accountability via breathalyzers and family involvement, and enhanced support gained through counseling skills. Findings reveal critical insights into intervention design for future implementation.